Macrolides for Reducing Acute Exacerbations of Chronic Obstructive Pulmonary Disease: New Evidence. Issue 1 (January 2016) - Djamin, Remco S.; Uzun, Sevim; Kluytmans, Jan A. J. W.; Hoogsteden, Henk C.; Aerts, Joachim G. J. V.; van der Eerden, Menno M.
Abstract : In the natural course of chronic obstructive pulmonary disease (COPD), exacerbations are important events influencing the outcome. Pharmacological and nonpharmacological interventions are available to reduce the exacerbation frequency. Despite these strategies to reduce exacerbations of COPD, there is still a subgroup of COPD patients who are experiencing exacerbations of COPD. Macrolide antibiotics may be an alternative therapy in this distinct subgroup of patients. This review describes the current understanding of the value of maintenance therapy with macrolides to reduce COPD exacerbations, according to recent studies. The positioning of macrolides in addition to the usual care, patient selection, and treatment regimen are discussed.